Kapalbhati changes cardiovascular parameters - Nayak, R; Prakash, S; Yadav, R K; Upadhyay-Dhungel, K (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Kapalbhati is among one of the cleansing act (shatkarma) in yogic philosophy. It is one of the popular Pranayama which has several benefits. It is highly recommended for those who have to do great deal of study and need a clean, clear mind. This study was conducted among nursing students at Janaki medical college, Janakpur, Nepal. Material and Methods: This analytical study was conducted among PCL Nursing students of Janaki Medical College, Janakpurdham, Nepal. Total 40 nursing student who gave consent and performed Kapalbhati correctly were included in the study. A detailed demographic profile with a structured questionnaire and observational checklist was filled for data collection. HR, SBP, DBP were the cardiac parameters taken. Those parameters were taken before, during, immediately after and after 1 minute, 2 minutes, 3 minutes and 5 minutes Pranayama. The data were entered in SPSS and Statistical analysis was done using version 20. Results: As in usual exercises, the HR, SBP and DBP increases significantly during Kapalbhati session but immediate post effect was surprisingly significantly fall in those parameters when compared with the value during exercises. The basal (pre-Kapalbhati) mean HR, SBP and DBP were 88.25 ± 9.02, 111.43 ± 11.28 and 73.9 ± 7.70 which increases upto 133.58 ± 35.70, 89.63 ± 23.31 and 118.55 ± 19.08 respectively during exercises and fall immediately after exercises value being 114.48 ± 21.94, 76.43 ± 15.34 and 88.6 ± 17.25 respectively. Conclusion: There is no significant difference between pre and post value of HR, SBP and DBP as in other study. There is significant rise between Pre-value and during-value of all parameters and significant fall of all parameters if compared between during-value and post-value. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (2): 43-49